PENGARUH FASILITAS, KUALITAS PELAYANAN DAN LINGKUNGAN FISIK TERHADAP KEPUASAN KONSUMEN MENGINAP DI HOTEL NEO EL TARI KUPANG - I Made Hadi Purnantara; I Wayan Eka Sudarmawan (Bajang Institute, 2024)
The focus of this research is to find out the effect of facilities, environment and service standards partially and simultaneously on customer satisfaction at Hotel Neo El Tari Kupang. The research was carried out at Hotel Neo El Tari Kupang, using 85 respondents as a sample. The Coefficient of Determination Test, F Test, and t Test were used in this work along with the Classical Assumption Test, Multiple Linear Regression Analysis, and F Test. as a technique in analyzing data. Through this research it was produced that simultaneously facilities, The physical atmosphere and service quality both significantly influence consumer happiness. Customer satisfaction is affected by facilities and service quality by a factor of 57.4%. The author gives advice to Hotel Neo El Tari Kupang to always provide complete and quality facilities according to what consumers need, provide maximum service and create an environment that is able to provide comfort for consumers.